Telomere length and mitochondrial DNA copy number in multidrug-resistant tuberculosis. (December 2021) - Freimane, Lauma; Barkane, Linda; Igumnova, Viktorija; Kivrane, Agnija; Zole, Egija; Ranka, Renate
Abstract: Multidrug resistant tuberculosis (MDR-TB) is a severe disease that requires prolonged chemotherapy and is associated with an increased probability of treatment failure and death. MDR-TB is a state of heightened oxidative stress and inflammation, which could be related to the aging-related processes and immunosenescence. We, therefore, tested the hypothesis that MDR-TB is associated with alterations in aging biomarkers in peripheral blood cells. We investigated 51 MDR-TB patients and 57 healthy individuals and carried out an analysis of covariance to assess the possible impact of different variables on biomarker perturbations. The results showed that MDR-TB patients had significantly reduced telomere length (TL) and increased mitochondrial DNA copy number (mtDNA CN) ( P  < 0.05) in comparison to the controls, and MDR-TB infection was the main influencing factor. Male sex and extrapulmonary TB strongly influenced mtDNA CN increment, and MDR-TB patients with normal weight had longer telomeres than those who were underweight ( P  < 0.05). In conclusion, the evidence for shorter telomeres and higher mtDNA CN in the peripheral blood cells of MDR-TB patients was obtained indicating the connection between MDR-TB and aging biomarkers. The observed associations highlight a complicated interplay between MDR-TB and immunosenescence, thus further studies are required to achieve full understanding.